Elucidating the performance and unexpected stability of partially coated water-splitting silicon photoanodes. Issue 9 (5th July 2018) - Oh, Kiseok; Mériadec, Cristelle; Lassalle-Kaiser, Benedikt; Dorcet, Vincent; Fabre, Bruno; Ababou-Girard, Soraya; Joanny, Loïc; Gouttefangeas, Francis; Loget, Gabriel
Abstract : In spite of the notorious instability of Si in alkaline solutions, Si partially covered with hemispherical Ni particles show striking performances for sunlight-assisted water oxidation. Abstract : H2 is an ideal energy carrier because it has a high energy density, and it can be easily stored, transported, and readily used to power electrical devices. Like photosynthesis, where photons are converted into energy-rich molecules, sunlight energy can be converted into H2 and O2 using photoelectrochemical water splitting cells (PECs). Despite the fact that silicon is considered one of the most attractive semiconductors for manufacturing photoelectrodes, its use is currently limited by its low activity and its instability in aqueous solutions. Herein, we report on surprisingly stable Si-based photoanodes, fabricated by simple aqueous electrodeposition, which results in the partial (<20%) coating of the Si surface with dispersed Ni nanoparticles (NPs). We show that photoelectrochemical activation considerably improves their performance by generating a high-activity catalytic shell around the Ni NPs. In addition, we demonstrate the stability of the photoanodes under various conditions in highly corrosive alkaline solutions in operation and in inactivity. The protection in operation is explained by anodic passivation, which generates a stabilizing SiO x layer. In contrast, the stability when no polarization is applied is unexpected because most of the Si, highly prone to etching, is in contact with the very corrosive aqueous phase. The experimental data allow us to propose a mechanism explaining this effect.